Use of Osteocutaneous Second-Toe Free Flap for Anterior Oronasal Fistulas. Issue 4 (October 2015) - Caterson, Edward J.; Singh, Mansher; Stephens, Willie; Pribaz, Julian J.
Abstract : Summary: Palatal fistula is a known complication of cleft lip–cleft palate repair. Fistulas anterior to the incisive foramen can be particularly difficult to repair because of the lack of available tissue. Adjacent tissue has inherent limitations, and multiple free-flap techniques have been described; however, there remains no single solution for this difficult problem. The authors present an alternative strategy of replacing "like with like" by using an osteocutaneous free tissue transfer of the second toe for anterior oronasal fistulas. Use of the osteocutaneous second-toe free flap provides skin lining to both the oral side and the nasal side to close oronasal fistulas. It also bridges the alveolar gap with vascularized bone. This flap can be considered as an elegant alternative for anterior oronasal fistulas.